Understanding the Concurrent Effect of the Building Facade Glazing Percentage and ‎Orientation on Energy Consumption of Schools in Iran - reza Amiri Fard; Mahmoud Reza saghafi; Mansoureh Tahbaz (صفه, 2021)
Orientation and the building facade glazing percentage are two parameters necessary ‎to be considered during the early stages of architectural design in order to determine the ‎location of the building on site and control the balance between the transparent and opaque ‎parts of its envelope. The aim of this research is‏ ‏to specify the optimum‏ ‏values of orientation and ‎glazing percentage of building facade and finding the effect of deviating the variables from the ‎optimum values on the total building energy consumption. The cases of this research are the ‎schools constructed based on the current standards and specifications of‏ ‏Iran’s Organization for ‎Renovating and Developing Schools in humid temperate climate. Due to interrelation between ‎these two parameters, their impacts are studied concurrently. Research questions are:‎ ‎1-What is the optimum orientation angle and facade glazing percentage of school buildings in ‎designated climate, in terms of the lowest energy consumption? 2-What is the sensitivity factor ‎of these variables in different situations on total energy consumption of the building? 3-What is ‎the differences of changes due to deviation from the optimum values, for each parameter? ‎ In this research the Latin Hyper-cube method is used for sampling the input values; and ‎Designbuilder program with Energy Plus simulation engine is used for modeling and analysis. ‎According to the results of this study south-facing buildings have the optimum orientation with ‎whatever glazing percentage. However, the optimum glazing percentage depends on the ‎building orientation and would differ from 40 to 55 percent. This study shows that increasing ‎the glazing percentage of school buildings up until 40 percent for east–oriented buildings has the ‎most significant sensitive effect on building energy consumption, whereas increasing it more ‎than this value didn’t show a considerable effect.